Organizational compassion: a conceptual extension and scale development - Akgun, Ali E.; Keskin, Halit; Basaran, Hatice T. Etlioglu (SPRINGER, 2025)
While the concept of compassion has been extensively explored at the individual level, this study takes a new approach by examining the compassion of organizations and, more specifically, the compassion capacity of organizations from an organizational culture perspective. This study develops a unique organizational compassion capacity scale through four field studies using an exploratory sequential mixed-methods research design. The findings unveil that organizational compassion capacity is a multi-dimensional construct with five dimensions: noticing, feeling, responding, collective action, and resource usage-related culture. This study further discusses the theoretical and practical implications of the findings.
Keywords: Organizational compassion capacity; Scale development; Organizational capacity; Compassion; FIT INDEXES; CONSEQUENCES; OTHERS; MANAGEMENT; CAPACITY; RESOURCE; EMPLOYEE; CONTEXT; EMPATHY; WORK; Psychology